2016
DOI: 10.1002/etc.3273
|View full text |Cite
|
Sign up to set email alerts
|

Metal contaminant accumulation in the hive: Consequences for whole‐colony health and brood production in the honey bee (Apis mellifera L.)

Abstract: Metal pollution has been increasing rapidly over the past century, and at the same time, the human population has continued to rise and produce contaminants that may negatively impact pollinators. Honey bees (Apis mellifera L.) forage over large areas and can collect contaminants from the environment. The primary objective of the present study was to determine whether the metal contaminants cadmium (Cd), copper (Cu), lead (Pb), and selenium (Se) can have a detrimental effect on whole-colony health in the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 55 publications
1
55
0
3
Order By: Relevance
“…We show that while ingestion of selenate inflicts mortality on all tested bumble bees, the microbiome‐inoculated bees have slightly reduced mortality, which on a wider colony level, may have a positive effect on resource‐gathering, colony hygiene, and ultimately overall colony health. Future research into the colony‐level effects of selenate poisoning on bumble bees should be investigated in a similar manner to the study by Hladun and and colleagues (), who showed that selenate had a deleterious effect on honey bee colony health.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We show that while ingestion of selenate inflicts mortality on all tested bumble bees, the microbiome‐inoculated bees have slightly reduced mortality, which on a wider colony level, may have a positive effect on resource‐gathering, colony hygiene, and ultimately overall colony health. Future research into the colony‐level effects of selenate poisoning on bumble bees should be investigated in a similar manner to the study by Hladun and and colleagues (), who showed that selenate had a deleterious effect on honey bee colony health.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Hladun et al found that honey bees ( Apis mellifera ) readily foraged on Raphanus sativus plants that were grown in seleniferous soil and collected pollen containing up to 2830 mg kg −1 selenium (Hladun et al, ). Accumulating selenium in the tissues of foraging honey bees has been shown to be detrimental to both the individual forager bees plus the health of the whole colony (Hladun et al, ; ; ). Metals may also have sub‐lethal effects on bees, as foraging efficiency is decreased when honey bees are exposed to manganese (Sovik et al, ) and bumble bees are exposed to nickel (Meindl and Ashman, ; ).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore worrisome that some populations of these important pollinators are declining in both Europe (3) and North America (4), with the main contributors of these declines thought to be habitat destruction, disease, and chemical exposure (5,6). While pesticides are considered to be the primary class of xenobiotics responsible for bee decline, foraging bees are exposed to additional environmental toxicants in floral nectar and pollen such as heavy metals (7), and oxidizers (8). The direct risks these chemicals pose to bees is not fully appreciated, furthermore, the indirect influences most chemicals (including pesticides) have on bee health is an understudied area (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers produce oxidizers (16) and sequester heavy metals (17) to protect themselves from parasites and herbivores respectively. The hive products of honey bees foraging on flowers that are growing in soils contaminated with selenium ions, copper, and/or cadmium have been shown to accumulate these pollutants at concentrations greater than in the flowers (7). So frequent is this exposure and accumulation of contaminants that honey bees have been proposed as bioindicators of soil contamination whereby testing the hives’ honey for metals will indicate the presence of local environmental toxins (18).…”
Section: Introductionmentioning
confidence: 99%
“…Along with other species, bee populations are declining around the world, most likely due to a combination of disease, pesticides, and land use change resulting in a lack of floral forage (4). Relatively unstudied stressors include the metals and metalloids that are harmful to bees and that can affect their overall health when bees forage on plants grown in contaminated areas (5,6). As bees may encounter various pollutants across environments (7), the capacity for diverse environmental stressors to affect bee health needs to be understood and mitigated.…”
mentioning
confidence: 99%